Comparison of supercritical fluid extraction using CO₂ on Patchouli leaves (Pogestemon cablin) benth essential oil and Soxhlet - Che Mohd Rosli, Muhamad Azarul Izham (2018)
Supercritical fluid extraction (SFE) of essential oil from dried Patchouli leaves (Pogestemon cablin) using CO₂ was reported in this work. Effect of pressure and effect of temperature towards yielding of patchouli essential oil in correlation towards quality of oil has been study. Process parameter was pursuing out under two different temperatures (40 OC and 80 OC) as well with three stages of pressure (100 bar, 200 bar and 300 bar). Result demonstrated that the extraction yield was increased as pressure increase from 1.13 % at 100 bar to 1.34 % at 200 Bar ultimately increased to 1.44 % at 300 Bar. For the temperature effect, the yield was decreased as the temperature increases, from 1.13 % at 40 OC to 0.24 % at 80 OC. For comparison purposes, patchouli leaves were extracted by Soxhlet extraction using absolute EtOH. Result showed that Sohxlet extraction provided a better yield (12 times better at 17.21 %) than supercritical fluid extraction, nevertheless the quality of the Patchouli essential oil was poor, 1 times lower with only 34.912 % patchoulol composition than supercritical fluid extraction